Correction to: Methods for trustworthy nutritional recommendations NutriRECS (Nutritional Recommendations and accessible Evidence summaries Composed of Systematic reviews): a protocol - Johnston, Bradley C.; Alonso-Coello, Pablo; Bala, Malgorzata M.; Zeraatkar, Dena; Rabassa, Montserrat; Valli, Claudia; Marshall, Catherine; El Dib, Regina [UNESP]; Vernooij, Robin W. M.; Vandvik, Per O.; Guyatt, Gordon H. (Springer Nature, 2019)
Following publication of the original article [1], the authors reported a change in the 'Competing interests' section as described below. 'Competing interests' in the original article:-BCJ, PAC, POV and GG are members of the GRADE working group. Remaining authors declare no competing interests. Revised 'Competing interests':-BCJ, PAC, POV and GG are members of the GRADE working group. In 2015, BCJ received funding from the International Life Science Institute to assess the methodological quality of nutrition guidelines using internationally accepted GRADE and AGREE guideline standards for a study titled The Scientific Basis of Guideline Recommendations on Sugar Intake: A Systematic Review [2]. The remaining authors declare no potential competing interests.
Correction to: Methods for trustworthy nutritional recommendations NutriRECS (Nutritional Recommendations and accessible Evidence summaries Composed of Systematic reviews): A protocol (BMC Medical Research Methodology (2018) 18 (162) DOI: 10.1186/s12874-018-0621-8)